Inkjet-Printed Flexible Active Multilayered Structures. (27th February 2017) - Trudeau, Charles; Bolduc, Martin; Beaupré, Patrick; Topart, Patrice; Alain, Christine; Cloutier, Sylvain
ABSTRACT: Active inkjet materials are invoked in the fabrication of optoelectronic devices. These types of multilayer assemblies contain a variety of commercially available ink formulations. It is envisioned that a dielectric SU-8 material can be used in a FET-like structure to form an interlayer between conductive silver and semi-conductive MWCNT-doped PEDOT:PSS ink layers. These printed structures may be fabricated onto a polyimide based flexible substrate, for instance. These structures are a starting point for offering valuable information on layer-on-layer printing interactions and interface problematics within a complete inkjet device fabrication.